Sustainability Assessment of Integrated Waste-to-Use Systems: A Case of Uganda - Agunyo, Miria Frances (The Global Environmental Engineers, 2022)
For countries like Uganda where organic waste composition accounts for at least 70% of the solid waste generated, collected, and disposed of at landfills and dumpsites, recovery of resources from the waste stream is crucial. This is because disposal of the waste in the landfills/dump sites exerts more pressure on land as a resource in addition to the environmental negative impacts associated with the degradation of the waste in the landfills, pollution of groundwater from leachate, generation of greenhouses gases, bad odor, and poor aesthetics. Moreover, given that the country also grapples with sewage and faecal sludge treatment and management due to the limited plants in place, alternative Waste-to-Use systems that promote resource recovery and management of various organic waste streams such as biowaste, animal manure, sewage/faecal sludge and wastewater could be a viable solution. The systems which consist of a combination of various technologies such as anaerobic digestion, incineration, landfilling, composting, and pyrolysis to produce briquettes boast of managing various organic waste streams and potential for application in various entities such as housing estates, towns/cities, at institutions. To assess the sustainability of such systems, multicriteria decision analysis was used. The results indicated that if trade-off of any aspect was considered i.e., technical, environmental, social, and financial, the Waste-to-Use systems were preferred i.e., a system consisting of composting and anaerobic digestion technologies. Also, a sustainability framework for the assessment of similar systems was proposed and it highlights the importance of involving stakeholders through the various stages such as, situation analysis, problem identification and definition, criteria and indictor selection, elicitation of scores and weight so that transparency in decision making can be boosted.